Potential for Novel Therapeutic Uses of Alpha Lipoic Acid - Fasipe, Babatunde; Faria, Andre; Laher, Ismail (Current Medicinal Chemistry, 2023)
Alpha-lipoic acid (ALA) is a potent antioxidant used in the management of diabetic neuropathy due to its ability to prevent neuronal lipid peroxidation. ALA also chelates transition metals, which can be beneficial in some diseases related to metal overload. Due to its unique antioxidant properties, ALA has potential novel applications in other diseases related to oxidative stress and inflammation. This review summarizes aspects of recent clinical trials and describes the uses of ALA in managing neuropathies. The unique pharmacological actions of ALA, coupled with relatively low toxicity, have led to several trials on the potential therapeutic uses of ALA in the management of diseases associated with increased oxidative stress, inflammation, and metal overload.
Keywords: lipid peroxidation